An introduction to the study of Indian history - Kosambi, D. D. (Damodar Dharmanand), 1907-1966 (2016)
"An Introduction to the Study of Indian History is a reprint of the second revised edition of a classic work on Indian history. As a fundamentally new approach to the study of Indian History, its scientific methodology, modern technique of interpretation, selection and analysis of basic problems make the presentation vivid and absorbing. Professor D.D. Kosambi has thrown open new fields for research. One of the principal tasks of this book is to serve as a critical guide to scientific historical thought. The work marks the highest level of approach to social, political and economic processes starting from the material plane. The reader is shown how to gain a profound insight into the past by examination of the monuments, customs and records which survive. At the same time, the present is shown to be the inevitable result of a steady historical development. Complete grasp of the material and mastery of detail shown in the survey of the movement from a pre-historic tribal society to the machine age, make this volume a unique contribution to contemporary historiography. The fruit of patient research and the mature reflection of a profoundly original mind, this volume is one of his major works, a scientific synthesis gained by unremitting search for fact and meaning. It is no exaggeration to state that this work on Indian history has earned universal recognition and honour"--Provided by publisher.
Preface to the revised edition -- Preface to the first edition -- Publisher's note -- Chronological outline -- Scope and methods -- The heritage of pre-class society -- Civilization and barbarism in the Indus Valley -- The Aryans in the Land of the Seven Rivers -- The Aryan expansion -- The rise of Magadha -- The formation of a village economy -- Interlude of trade and invasions -- Feudalism from above -- Feudalism from below -- Appendix: The making of history (illustrations) -- Commentary to the illustrations.
"First published in 1956 by Popular Prakashan Pvt. Ltd"--Title page verso.
Includes bibliographical references and index.
Keywords: India -- History